IMPLICATION OF INVESTMENT LEGAL POLITICAL DYNAMICS ON THE INVESTMENT CLIMATE IN INDONESIA - Rohmat Rohmat (Law Review, 2022)
This article is to analyze and examine the dynamics of investment law politics that can provide legal certainty for investors, both domestic and foreign investors. Legal politics is an integral part in making a statutory regulation. The existence of such legal politics will bring the substance of a regulation into the initial purpose and spirit of the formation of legislation. This research was conducted normatively using secondary data. Secondary data used in the form of primary legal materials and secondary legal materials. After the data was obtained in the literature, the data were then analyzed descriptively qualitatively to produce conclusions in this study. The conclusion in this study is that the investment law politics in each era of the old order, new order era, and reform era has its own characteristics according to the developments and demands of the times. In the old order era, the focus was more on finding capital for development and national interests, while in the reform era investment became an additional element in national development. The Job Creation Act brings the spirit of ease in investing.